2020
DOI: 10.1371/journal.pone.0228269
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between lipid and glycemic levels in an Indian population: A bidirectional Mendelian randomization approach

Abstract: Background Dyslipidemia and abnormal glycemic traits are leading causes of morbidity and mortality. Although the association between the two traits is well established, there still exists a gap in the evidence for the direction of causality. Objective This study aimed to examine the direction of the causal relationship between lipids and glycemic traits in an Indian population using bidirectional Mendelian randomization (BMR). Methods The BMR analysis was conducted on 4900 individuals (2450 sib-pairs) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(70 reference statements)
0
5
0
1
Order By: Relevance
“…In the study by Sobrin et al., 8 there was no evidence of genetically predicted plasma lipid levels being associated with risk of diabetic retinopathy in Chinese ancestry populations. In a bidirectional MR study exploring the causal relationships between lipid and glycemic levels in Indian population by Agarwal et al., 31 the authors report evidence of only genetically predicted TG levels being associated with glycemic traits.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Sobrin et al., 8 there was no evidence of genetically predicted plasma lipid levels being associated with risk of diabetic retinopathy in Chinese ancestry populations. In a bidirectional MR study exploring the causal relationships between lipid and glycemic levels in Indian population by Agarwal et al., 31 the authors report evidence of only genetically predicted TG levels being associated with glycemic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong intercorrelation between blood lipids and insulin resistance has been well documented, 19–21 the temporal relationship between them is not elucidated completely. The current study explored the temporal relationship between blood lipids and insulin resistance in a longitudinal cohort of perimenopausal women using cross-lagged path analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Mendelian randomization analysis confirmed the causal effect of TG on insulin resistance. 19 Elevated TG are frequently accompanied by elevated free fat acid (FFA), then the elevated FFA will affect insulin resistance through the glucose-fatty acid cycle. 25 Glucose-fatty acid cycle, also called Randle cycle, refers to the significant reduction in the uptake and utilization of glucose that occurs in muscle when fatty acid oxidation is intense, accordingly, the insulin resistance may increase.…”
Section: Discussionmentioning
confidence: 99%
“…IR is a key factor in the pathogenesis of obesity and T2DM, and several studies have shown a link between IR and adipose tissue indicators, including leptin and adiponectin. [14][15][16] Therefore, this research aims to examine how leptin and adiponectin levels affect IR, IS, BMI, WC, and AIP in Saudi women with T2DM. This is the first research on Saudi females that studied leptin and adiponectin levels in T2DM, including obesity and CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%